The Effect of Dribbling Training on Basic Handball Skills of Sports and Health Education Students - Muhammad prawibowo; Alfarizi, Muhammad; Septiani, Indri; Putriani, Dian; Farizal Saputra; Mulyadi, Sandi Hidayutul (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2025)
In the Handball course for the 2021 cohort, students were found to have suboptimal performance, particularly in basic skills such as dribbling. This study aims to examine the effect of dribbling training (X) on handball basic skills (Y). The research employed an experimental method with a one-group pretest–posttest design. The population consisted of 43 PORKES students from the 2021 class, and purposive sampling was applied to include only male participants, resulting in a sample of 12 students. The research instrument used a 40-meter dribbling test developed by Susanto. Data analysis used an independent t-test with a significance level of α = 0.05. The results indicated a significant improvement in students’ dribbling performance, with an average time reduction of 7.19 seconds, from 19.27 seconds in the pre-test to 12.08 seconds in the post-test. Statistical analysis showed tcount = 24.623 > ttable = 1.796, confirming a significant effect of the dribbling training. It can be concluded that dribbling training has a positive and significant effect on improving basic handball skills among Sports and Health Education students at Pasir Pengaraian University.